The 'Face' of Indonesian Cosmetics: Investigating Language Choices in Local Brand Advertisement Boards and Consumers' Preferences - Khazanah, Dewianti; Kusumaningputri, Reni; Sampurna, Hadi; Setiarini, Riskia; Anam, Syamsul (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2023)
English has been extensively chosen by multinational companies for the purpose of advertising cosmetics in expanding circle countries. However, studies focusing on the language choices made by Indonesian local cosmetic companies for their advertisement boards and the consumers’ preferences regarding these choices are scanty. The goals of this study, thus, are double-layered. First, the choices of language in each element of the advertisement board copywriting- brand and product names, taglines, slogans, and product descriptions- were revealed. Second, the consumers’ preferences regarding language choices on each of these elements were explored. The language choices were revealed by scrutinizing 98 collected local cosmetic advertisement boards using the types of language choice by da Silva (2017). Preferences were gathered using a survey adapted from Hornikx et al. (2010) and da Silva (2014) and were explored using thematic analysis. The findings show that English dominated all elements of copywriting in the local cosmetic advertisement boards- in brand and product names, taglines, slogans, and descriptions. The study, however, pointed out the gap between the domination of English and consumers’ preferences. A significant number of people chose Bahasa Indonesia as the voice for these advertisements mainly in the aspect of slogans and brand names. The findings show that the choice of Bahasa Indonesia in brand names was more preferable as it projected the products’ national identity in the global market and consumers’ national pride. The same preference was also found in the product descriptions as most consumers deemed Bahasa Indonesia to promote better understandability. These findings suggest that Indonesian cosmetic companies’ language choice policy for product advertisements needs to be revisited.